Artocarpus heterophyllus Lam. stem bark inhibits melanogenesis through regulation of ROS, cAMP, and MAPK Pathways - Hazwani Mat Saad; Chun, Hoe Tan; Sugumaran Manickam; Siew, Huah Lim; Kae, Shin Sim (Penerbit Universiti Kebangsaan Malaysia, 2023)
Natural-based skin-lightening cosmeceutical products are attracting high popularity nowadays due to their relatively high bioavailability upon application. Artocarpus species have been highlighted with such potential, and our previous studies have reported that Artocarpus heterophyllus Lam. stem bark extract exhibited a potent anti-melanogenic activity by reducing melanin content and inhibiting cellular tyrosinase activity in B16F10 melanoma cells. Hence, this study aimed to identify the bioactive fraction from A. heterophyllus Lam. stem bark and determine its anti-melanogenic mechanisms in B16F10 melanoma cells. Our results showed that a fraction (H-3) demonstrated the most pronounced anti-melanogenic effect at 12.00 µg/mL by reducing melanin content to 22.86 ± 2.90% and inhibiting cellular tyrosinase activity at treatment concentration 33-fold lower than kojic acid, without being cytotoxic against B16F10 melanoma cells. Moreover, treatment with H-3 for 24 and 48 h substantially scavenged intracellular reactive oxygen species (ROS) of hydrogen peroxide-challenged B16F10 melanoma cells by 1.8 and 4.4%, respectively. Based on the microarray profiling and qPCR analysis, H-3 downregulated Creb3l1, Creb3l2, Creb3l3, Mitf, Tyr, Tyrp1, and Dct genes in B16F10 melanoma cells, whereas the expression of Map3k20, Mapk14 (p38), and Foxo3 genes was markedly increased. Altogether, these results demonstrated that H-3 exhibited its anti-melanogenic activity in B16F10 melanoma cells through scavenging ROS and concurrent inhibition of the cAMP and activation of the p38/MAPK signaling pathways. These findings indicate that H-3 has the potential to be used as a skin lightening cosmeceutical agent in the treatment of skin hyperpigmentation.